PENERAPAN MODEL PEMBELAJARAN SELF ORGANIZING LEARNING ENVIRONMENT (SOLE) TERHADAP KEMAMPUAN LITERASI GURU PAUD - Luluk Asmawati; Sholeh Hidayat; Cucu Atikah (Balai Besar Guru Penggerak Jawa Timur, 2021)
This study aims to verify the effect of the SOLE learning model on the literacy skills of Early Childhood Education Teachers in Banten Province. This research is quantitative research with a quasi-experimental type. The subjects of this study were Early Childhood Education Teachers Teachers in Banten Province. The research data collection technique was in the form of a test instrument. The data validity used content and construct validity. The data analysis technique used variance analysis. The results showed that there was an effect of the SOLE learning model on the literacy skills of Early Childhood Education Teachers teachers in Banten Province. The descriptive analysis of teacher activity shows that the experimental class (SOLE learning model) is better than the control class (conventional model). The conclusion of this study is that the SOLE learning model has an effect on improving the literacy skills of Early Childhood Education Teachers teachers.AbstrakPenelitian ini bertujuan untuk menguji pengaruh model pembelajaran SOLE terhadap kemampuan literasi guru PAUD di Provinsi Banten. Penelitian ini merupakan penelitian kuantitatif dengan jenis kuasi eksperimen. Subjek penelitian ini yaitu guru PAUD di Provinsi Banten. Teknik pengumpulan data penelitian ini berupa instrument tes. Validitas data menggunakan validitas isi dan konstruk. Teknik analisis data menggunakan analisis variansi. Hasil penelitian menunjukkan bahwa ada pengaruh model pembelajaran SOLE terhadap kemampuan literasi guru PAUD di Provinsi Banten. Analisis aktivitas guru secara deskriptif memperlihatkan bahwa kelas eksperimen (model pembelajaran SOLE) lebih baik daripada kelas control (model konvensional). Simpulan penelitian ini yaitu model pembelajaran SOLE berpengaruh meningkatkan kemampuan literasi guru PAUD.